The structures and electronic properties of zigzag silicene nanoribbons with periodically embedded with four- and eight-membered rings. (July 2018) - Tan, Guiping; Lu, Junzhe; Zhu, Hengjiang; Li, Fangfang; Ma, Miaomiao; Wang, Xiaoning
Abstract: Using density functional theory (DFT), we have studied the structure of a zigzag silicene nanoribbons (SiNRs) with periodically embedded with four- and eight-membered rings, and studied their electronic properties by calculating its band structures and density of states (DOS). The results showed that the zigzag SiNRs have a sp 2 hybridization, in addition, the band gap gradually decreased with the increase of the width by layer, and gradually changed from semiconductor properties to metal properties. The existence of vacancy defects increased the band gap and energies, but their positions could not change the structure and the electronic properties. Graphical abstract: Highlights: The electronic properties of SiNRs is different from width and edge shape. With the increase of width, the band gap decrease by fluctuation. The position of the vacancy defects could not change the structure and electronic properties